2021
DOI: 10.1111/jace.17998
|View full text |Cite
|
Sign up to set email alerts
|

Conduction properties of Ti‐doped NaTaO3 at intermediate temperature

Abstract: In this work, the ionic conductivity and charge carriers of acceptor-doped sodium tantalate (NaTaO 3 ) with perovskite structure were investigated at intermediate temperatures. The Ta-site of NaTaO 3 was doped with up to 20% titanium (Ti) with the conventional solid-state reaction method. After calcination at 900°C, samples nominally doped with 5, 10% Ti show X-ray diffraction (XRD) pattern of orthorhombic NaTaO 3 only, while peaks of Na 2 Ti 3 O 7 can be observed in those doped with 15, 20% Ti. The conductivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…For example, high oxide‐ion conductivities were observed in acceptor‐doped sodium and potassium niobates, NaNbO 3 and KNbO 3 , 10–12 and potassium tantalate, KTaO 3 , was reported to exhibit proton conductivity by Cu or Fe doping 7–9 . In our recent study, 14 we have confirmed the proton conductivity in titanium‐doped sodium tantalite (Ti‐doped NaTaO 3 ) at intermediate temperatures. By Ti‐doping, oxygen vacancies, VnormalO$V_{\rm{O}}^{ \bullet \bullet }$, are introduced into the crystal, and Ti‐doped NaTaO 3 hydrates in humidity, generating proton charge carriers.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…For example, high oxide‐ion conductivities were observed in acceptor‐doped sodium and potassium niobates, NaNbO 3 and KNbO 3 , 10–12 and potassium tantalate, KTaO 3 , was reported to exhibit proton conductivity by Cu or Fe doping 7–9 . In our recent study, 14 we have confirmed the proton conductivity in titanium‐doped sodium tantalite (Ti‐doped NaTaO 3 ) at intermediate temperatures. By Ti‐doping, oxygen vacancies, VnormalO$V_{\rm{O}}^{ \bullet \bullet }$, are introduced into the crystal, and Ti‐doped NaTaO 3 hydrates in humidity, generating proton charge carriers.…”
Section: Introductionsupporting
confidence: 73%
“…Conventionally, the tilting of TaO 6 octahedra and the anisotropy of the crystal structure are supposed to result in a deteriorated conductivity 17 . However, the measured conductivity of Ti‐doped NaTaO 3 is reported to be the highest class among all the reported I – V perovskite ceramic, 14 which means there might be some ignored mechanism promoting proton conduction in Ti‐doped NaTaO 3 . Some previous researches have theoretically investigated the proton conduction mechanism in orthorhombic perovskites CaZrO 3 and SrZrO 3 by first‐principles calculations 18–21 .…”
Section: Introductionmentioning
confidence: 99%
“…Different from undoped samples, both 1% Ti‐doped samples have a greatly enhanced conductivity in a wet atmosphere, confirming the proton conduction generated by Ti‐doping. Same as demonstrated in our previous study, 20 there is supposed to be oxygen vacancy (VnormalO$V_{\rm{O}}^{ \bullet \bullet }$) generated by Ti doping (Equation ). In this work, samples were sintered at 1200°C in dry O 2 , in which TiO 2 is quite stable and low oxygen partial pressure is necessary for the existence of Ti 2+ or Ti 3+ .…”
Section: Resultsmentioning
confidence: 73%
“…Therefore, the higher conductivity of Na‐deficient sample can be attributed to the increased charge carrier VNa$V_{{\rm{Na}}}^{\rm{^{\prime}}}$, VnormalO$V_{\rm{O}}^{ \bullet \bullet }$, and/or electronic carriers. In our previous work, 20 the undoped sample Na0.974 shows increased conductivity with hole conduction in high p (O 2 ) (Equation ), but the increase is limited and the ionic conduction is still dominant: 2NaNa×badbreak+normalOO×goodbreak=2VNagoodbreak+VOgoodbreak+normalNa2O\begin{equation}2{\rm{Na}}_{{\rm{Na}}}^ \times + {\rm{\;O}}_{\rm{O}}^ \times = 2V_{{\rm{Na}}}^{\rm{^{\prime}}}{\rm{\;}} + V_{\rm{O}}^{ \bullet \bullet } + {\rm{N}}{{\rm{a}}_2}{\rm{O}} \uparrow \end{equation} 2VO··badbreak+O2goodbreak=2OO×goodbreak+4h·\begin{equation}2V_{\rm{O}}^{ \cdot \cdot } + {\rm{\;}}{{\rm{O}}_2} = {\rm{\;}}2{\rm{O}}_{\rm{O}}^ \times + 4{{\rm{h}}^ \cdot }\end{equation}…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation